Knowledge Democracy and Epistemic In/Justice: Reflections on a Conversation - Hall, Budd L.; Godrie, Baptiste; Heck, Isabel (Canadian Journal of Action Research, 2020)
The focus of the article is on how knowledge is created, who creates knowledge, how knowledge is co-constructed, whose knowledge is excluded and how knowledge is being used to challenge inequalities and strengthen social movement capacity. This article grew from a fascinating conversation that the three of us had in Montreal in September of 2019. We decided to share our stories about knowledge and justice with a wider audience in part as a way for us to reflect further on the meaning of our initial conversation, but also to invite others into the discussion. Baptiste Godrie works in a research centre (CREMIS) affiliated with Quebec’s health care and social services system, Isabel Heck works with the anti-poverty organization Parole d’excluEs, both affiliated to universities, and Budd Hall works at the University of Victoria and is the Co-Chair of the UNESCO Chair in Community-Based research and social responsibility in higher education.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; amériques; connaissances; discipline; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; épistémologie